Dividends, Share Repurchases, and the Substitution Hypothesis - Grullon, Gustavo; Michaely, Roni (Journal of Finance, 2002)
ABSTRACT We show that repurchases have not only became an important form of payout for U.S. corporations, but also that firms finance their share repurchases with funds that otherwise would have been used to increase dividends. We find that young firms have a higher propensity to pay cash through repurchases than they did in the past and that repurchases have become the preferred form of initiating a cash payout. Although large, established firms have generally not cut their dividends, they also show a higher propensity to pay out cash through repurchases. These findings indicate that firms have gradually substituted repurchases for dividends. Our results also suggest that before 1983, regulatory constraints inhibited firms from aggressively repurchasing shares.